The notion of living creature in John Dewey’s cultural naturalism - Luque Moya, Gloria (Estudios de Filosofía, 2019)
The term ‘naturalism’ is problematic in the current context since it comprises a set of very different philosophical traditions and thinkers. Some contemporary authors, such as David Papineau, have proposed grouping them according to two different components: the ontological component, which is concerned with the contents of reality; and the methodological one, which is concerned with the way of investigating reality. In general terms, John Dewey’s naturalism, the same as Perice’s and Rorty’s ones, has been defined as methodological. However, through the analysis of the notion of living creature, this article attempts to show how Deweyan naturalism also needs to be understood from its ontological dimension. First, it deals with the different philosophical currents and authors which contribute to the evolution from the Deweyan term of organism to the living creature. Then, it outlines the continuity between the creature and its surroundings that affirms Dewey’s emergent ontology and the potential of this interaction.